The recruiter : a Rick Carter novel - Podolski, Gregg (Blackstone Publishing, 2024)
An action-packed debut from Gregg Podolski, The Recruiter is a thrilling and unique adventure through the European underworld. When bad guys need good help, they call Rick Carter. He's a criminal recruiter, searching for contract killers, cyber hackers, gun smugglers, and any other assorted villains-for-hire a European crime boss might need. But, when the family he left behind in New Jersey is caught up in a client's plot to monopolize the black market, Rick has to save them from two of his own top candidates: deadly assassins known only as Ghost and The Persian. Fixing his own mess will require a set of skills he doesn't have--not a problem, as finding qualified help is where he excels. But stepping into action, becoming the hero his family needs, that's new territory. For a man who's spent the last ten years being the best at helping the worst, this may be his last chance to do something right.